The perception of micro-enterprises on the constraints encountered in research and development (R&D): Evidence from Malaysia - Abd Hamid, Nadiah; Ghazali, Noorlaila; Syafinaz Shaffee, Nor; Ibrahim, Zuraeda; Mohd Norfadzilah, Nik (Edelweiss Applied Science and Technology, 2024)
Engagement in research and development (R&D) is crucial not only for large companies but also for micro businesses. For micro enterprises, R&D can lead to innovation, which enable the development of new products and improve existing ones. This innovation is vital for micro-enterprises to stay competitive and build on their ability to meet the customers’ evolving needs. Potentially, R&D also helps micro businesses enhance their operational efficiency, reduce costs, and adopt sustainable practices, which are all essential for long-term viability. Unfortunately, micro-enterprises often encounter significant difficulties in engaging with R&D activities. Past studies have highlighted on the primary barriers for micro-enterprise to get involve with R&D such as limited financial resources, lack of access to advanced technology, and insufficient expertise. This paper examines the hurdles faced by Malaysia’s micro-enterprises in engaging with R&D activities. A questionnaire survey was conducted and 2,000 questionnaires were distributed, with 202 usable responses available for analysis. The study found that the availability of financial incentives for asset and working capital needs are positively viewed, but difficulties persist in securing loans for modern agriculture, digital transformation, and Shariah compliant businesses. While R&D boosts business growth and competitiveness, its impact on reducing operational costs and ensuring sustainability are unclear. Incubator centers provide valuable support but the lack of comprehensive mentorship programs has imposed difficulties for micro-enterprises to utilize the facilities. The findings give a clear indication to policymakers that enhancing support mechanisms is crucial in order to fully leverage the financial and R&D incentives for micro-enterprises.